Pengaruh Warna Primer Terhadap Working Memory Pada Mahasiswa Universitas Muhammadiyah Bandung - Fauzan, Rendy Luqman; Firdaus, Lala Khaerun Nisa; Purnomo, Adrian Putera; Luthfiyana, Zahro Atharekha (IBERS : Jurnal Pendidikan Indonesia Bermutu, 2024)
This research specifically examines the effect of primary colors on working memory in students at the Muhammadiyah University of Bandung. Many studies have been conducted to examine this, one of which is that color can increase concentration and affect working memory. This study used an experimental method involving 40 students who were divided into 2 groups. 20 students in the control group were given colorless images, and 20 students in the experimental group were given colorless images. Participants in this study were aged 17-23 years and did not have color blindness. The results of this study indicate that the hypothesis is rejected, there is no effect of color exposure on working memory.